Cerpen “Perempuan Pala” Karya Azhari: Pendekatan Mimetik - Mariyatul Kiptiyah (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
The purpose of this research is to reveal the types of social aspects in the short story "Perempua Pala" by Azhari and to reveal the phenomena that exist in the short story "Perempuan Pala" by Azhari which is a reflection of social phenomena in the real world toward Acehnese society when the Dutch colonized and new regime reign. This study used a qualitative approach and uses the concept of character and characterization as well as the mimetic theory to reveal phenomena that exist in the story. Data collection techniques used in this research is documentation, i.e. library documentation. With the steps; read the text carefully, symbolized the data, and recorded the data that related to the focus of research. The data source of this research is short story "Perempuan Pala" by Azhari published by AKY Press in 2004. In line with the purpose of research, the results of this research is revealed, that there are four types of social aspects in the short story "Perempuan Pala" by Azhari, as follows: (1) the suffering of Acehnese society in the Dutch colonial era, (2) Conflict of Acehnese society, (3) Independence of Acehnese society, and (4) The peace of Acehnese society. Phenomena that occurred in the short story "Perempuan Pala" by Azhari is a reflection of a real phenomenon that occurs in Acehnese society that stricken a long conflict from Dutch colonial era until the new regime reign. Mala wishes a peace created on Aceh Earth, violence and oppression come to the end so that Acehnese society can feel the peace and freedom, which in the end, the men came down from the mountain. Government of the regime also wanted to create peace in Aceh. With the efforts made by the government through a persuasive approach to the Acehnese and negotiations were conducted with high-ranking of GAM, eventually the peace created on Aceh Earth.